Handbook on fact-finding and documentation of human rights violations, based on a workshop ... 1-6 October 1993, Chiangmai, Thailand - Guzman, Manuel; Ignacio, Johannes L.; Ravindran, D.J. (Bangkok Asian Forum for Human Rights and Development (FORUM-ASIA) and Union for Civil Liberty-Thailand, 1994)
The purpose of the handbook is to help human rights organizations in undertaking systematic fact-finding and documentation of human rights violations and thereby strengthening their role in protection of human rights.
Based on the proceedings of a workshop about the subject held in Chiangmai, Thailand. Intended for the use of local human rights organizations engaged in fact-finding and documentation of human rights violation. Identifies basic elements involved in the subject. Provides practical recommendations and propositions in facilitating organizations in classifying their collections and documentations of information on human rights violation.